Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. Join them; it only takes a minute:

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

The theorem is this: If $\mu$ is a positive regular Borel measure on the unit circle, then a closed subspace $\mathcal{M}$ of $L^2(\mu)$ satisfies $\chi_1 \mathcal{M}=\mathcal{M}$ if and only if there exist a Borel subset $E$ of the unit circle such that $\mathcal{M}=L_E^2(\mu)=\{f\in L^2(\mu):f(e^{it})=0 \text{ for } e^{it}\notin E\}$ where $\chi_1(e^{it})=e^{it}$.

In the proof, they show that the projection onto $\mathcal{M}$ is of the form $M_\phi$ for some $\phi\in L^\infty(\mu)$. Then they say that the result then follows. I am not seeing why the result then follows.

share|cite|improve this question

$M_\phi$ is a projection, so $M_\phi = M_\phi^2$. Since $M_f M_g = M_{fg}$ it follows that $M_\phi^2 = M_{\phi^2}$. Therefore $M_\phi = M_{\phi^2}$, so that $\phi^2 = \phi$ a.e. and hence $\phi(x) \in \{0,1\}$ for a.e. $x$. This means that $\phi$ is a.e. equal to a characteristic function, say $\phi = \chi_E$.

Since for $f \in \mathcal{M}$ we have $f = M_\phi f = \chi_E f$, it follows that $f(x) = \chi_E(x) f(x) = 0$ for $x = e^{it} \notin E$. On the other hand, $f(e^{it}) = 0$ for $e^{it} \notin E$ implies that $\chi_E f = f$, so $\mathcal{M} = \{f\in L^2(\mu):f(e^{it})=0 \text{ for } e^{it}\notin E\}$.

share|cite|improve this answer

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.